Investigating College Students' Intentions to Seek Online Counseling Services. Issue 4 (7th August 2020) - Wang, Xiaojing (Romy); Joyce, Nick; Namkoong, Kang
ABSTRACT: The prevalence and severity of mental health issues among students have been increasingly talked about on campuses in recent years. The Internet has rapidly developed to deliver information and facilitate online communication, which creates online counseling to meet the mental health needs of college students. Using the Theory of Planned Behavior, this study examines college students' intentions to seek both face-to-face and online counseling. An online survey was conducted with 440 college students. Results suggest that subjective norms, attitudes, and perceived behavioral control predicted participants' intentions to seek counseling. Although face-to-face counseling was generally seen as most appealing, this effect was moderated by different levels of self-stigma, stigma by close others, and communication competence, such that higher self-stigma, stigma by close others, and lower communication competence made face-to-face counseling less attractive compared to online counseling.